2014
DOI: 10.4161/auto.28390
|View full text |Cite|
|
Sign up to set email alerts
|

The role of GABARAPL1/GEC1 in autophagic flux and mitochondrial quality control in MDA-MB-436 breast cancer cells

Abstract: GABARAPL1/GEC1 is an early estrogen-induced gene which encodes a protein highly conserved from C. elegans to humans. Overexpressed GABARAPL1 interacts with GABAA or kappa opioid receptors, associates with autophagic vesicles, and inhibits breast cancer cell proliferation. However, the function of endogenous GABARAPL1 has not been extensively studied. We hypothesized that GABARAPL1 is required for maintaining normal autophagic flux, and plays an important role in regulating cellular bioenergetics and metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 63 publications
3
77
0
Order By: Relevance
“…Autophagy is involved in recycling of damaged cellular organelles, including mitochondria. It is the primary mechanism for removing damaged mitochondria and plays an important role in maintaining mitochondrial homeostasis in cells [5658]. Reports show that inhibition of autophagy results in accumulation of damaged mitochondria [3133].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is involved in recycling of damaged cellular organelles, including mitochondria. It is the primary mechanism for removing damaged mitochondria and plays an important role in maintaining mitochondrial homeostasis in cells [5658]. Reports show that inhibition of autophagy results in accumulation of damaged mitochondria [3133].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR was performed using SYBR green in an ABI 7500 machine. Mitochondrial DNA copy number was determined by normalizing results from primers targeted to mtDNA (Forward: 5'-CCAAGGAATTCCCCTACACA-3' and Reverse: 5′-GAAATTGCGAGAATGGTGGT-3′) against results from primers targeted to nuclear 18S DNA (Forward: 5'-CGAAAGCATTTGCCAAGAAT-3' and Reverse: [38], [39]. Mitochondrial DNA damage was determined by PCR as previously described [40].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Novak et al . (4143) found that GABARAPL1 colocalizes with depolarized mitochondria during basal, starvation, and apoptotic conditions. GABARAPL1 deficiency attenuates autophagic flux including mitophagy and results in accumulation of damaged mitochondria (43).…”
Section: Functions Of Lc3/gabarap Family Proteins In Autophagymentioning
confidence: 99%